Effect of Exercise Training on Bone Mineral Density in Post-menopausal Women: A Systematic Review and Meta-Analysis of Intervention Studies - Shojaa, Mahdieh; Von Stengel, Simon; Schoene, Daniel; Kohl, Matthias; Barone, Giuseppe; Bragonzoni, Laura; Dallolio, Laura; Marini, Sofia; Murphy, Marie H.; Stephenson, Aoife; Mänty, Minna; Julin, Mikko; et al. (Frontiers in Physiology, 2020)
Osteoporosis is a major health problem in postmenopausal women (PMW). Exercise training is considered a cost-effective strategy to prevent osteoporosis in middle aged-older people. The purpose of this study is to summarize the effect of exercise on BMD among PMW. A comprehensive search of electronic databases was conducted through PubMed, Scopus, Web of Science, Cochrane, Science Direct, Eric, ProQuest and Primo. BMD changes (standardized mean differences: SMD) of the lumbar spine (LS) femoral neck (FN) and/or total hip were considered as outcome measures. After categorization, statistical methods used to combine data and compare subgroups. 75 studies were included in this systematic review and meta-analysis. The pooled number of participants was 5300 (intervention group: 2901, control group: 2399). The majority of studies employed weight bearing aerobic exercise, dynamic resistance exercise or a combination of both. The pooled estimate of random effect analysis was SMD=0.37, 95%-CI: 0.25-0.50, SMD=0.33, 95%-CI: 0.23-0.43, and SMD=0.40, 95%-CI: 0.28-0.51 for LS, FN, and total Hip-BMD respectively. In the present meta-analysis, there was a significant (p<0.001), but rather low effect (SMD= 0.33-0.40) of exercise on BMD at LS and proximal femur. We further observed a large variation among the single study findings, with highly effective studies but also studies that trigger significant negative results. This finding can be largely attributed to differences among the exercise protocols of the studies. We conclude that the true effect of exercise on bone is diluted by a considerable amount of studies with inadequate exercise protocols.